Budaya Toleransi Antar Umat Beragama di Desa Pademonegoro Kecematan Sukodono Kabupaten Sidoarjo - A. Syafi' AS.; Mishbahush Shudur; Moch Hasiburochman (Sumbula: Jurnal Studi Keagamaan, Sosial dan Budaya, 2022)
Humans were created by God as individual beings and social beings or social beings. In living their social life, it is undeniable that there will be frictions between groups of people, both related to race and religion. So this study seeks to find a cultural of tolerance between religious communities in Pandemonegoro village, Sukorame sub-district, Sidoarjo district. This research is descriptive qualitative. The data collection technique uses observation, interviews and documentation data in the form of literature and the results of previous research. While the data analysis uses data reduction, data display (data display), and conclusion drawing or verification. The results showed that the role of community leaders in forming a culture of tolerance between religious communities in the village of Pademonegoro, Sukodono sub-district, Sidoarjo district was as a channel for the aspirations of their religious people to other religious leaders in an effort to maintain religious harmony in order to reach mutual agreement through deliberation.